Immunotherapy‐refractory vacuolar myopathy with mucin deposition in scleromyxedema: A possible role of fibroblast growth factor 2. Issue 5 (19th May 2020) - Yanagihara, Yuki; Hayashi, Shintaro; Koge, Junpei; Honda, Hiroyuki; Yamasaki, Ryo; Yamada, Yuichi; Oda, Yoshinao; Iwaki, Toru; Kira, Jun‐ichi
Abstract : Scleromyxedema (SME) is characterized by widespread waxy papules on the skin, with mucin deposits in the upper dermis. Twenty‐one SME cases of myopathy have been reported; of the cases, six showed vacuolar formation, and two showed mucin deposition. We report the first case of SME with mucin‐associated vacuolated fibers. A 45‐year‐old woman with SME developed progressive proximal muscle weakness. Muscle biopsy revealed myopathic changes with numerous vacuoles linked to mucin in the affected muscle fibers, which were heavily immunostained for fibroblast growth factor 2 (FGF2). Despite repeated high dose oral prednisolone and intravenous immunoglobulin administrations, muscle weakness recurred continuingly, culminating in death due to congestive heart failure. Immunotherapy was partly effective in our case, although it was refractory. Treatment responsiveness in patients with SME myopathy varied; however, due to its rarity, the mechanism remains to be elucidated. To address this issue, we investigated muscle specimens immunohistochemically and detected marked upregulation of FGF2 in the affected muscle fibers of our patient. FGF2, a strong myogenesis inhibitor, may exert a suppressive effect on muscle fiber regeneration, which may have conferred refractoriness to our patient's SME myopathy.